Сага о Форсайтах: перевод с английского (Джон Голсуорси) - Голсуорси Джон (Семейная библиотека, 1993)
Экземпляры: (20210527) / Инвентарный номер: 26015 / Цена: / Сис.шифр: 84(4Вл)6-444 / Авт.знак: Г 61 / ББК: 84(4Вл)6-444